Relevance of high and low cash holdings by corporations in Malaysia and Korea to efficiency, valuation and risks - Soh, Wei Ni (2015)
Cash is the most liquid asset in any firm’s balance sheet and is seen as a very important component in facilitating day-to-day business transactions in firms. Prior studies have examined the appearance of agency costs in firms which hold large amounts of cash, suggesting several solutions to mitigate the costs on shareholders. Surprisingly, few if not none, have studied the efficiency of cash in generating firm earnings, which directly contribute to shareholders’ wealth. This study examines three objectives involving corporate cash holdings from two selected Asia-Pacific countries, namely South Korea and Malaysia, with data from 2001 to 2012. These objectives include estimating cash holdings that contribute to firm efficiency, estimating the value of cash holdings and optimal cash level through shareholders’ valuations, and investigating the impact of internal and external risk factors toward cash holdings. The first objective employs data envelopment analysis (DEA) estimation and two-stage regressions model. The findings conclude that the firm size, firm growth, and gross domestic product (GDP) are statistically significant for firm efficiency in both markets. The cash holdings help improve firm efficiency as the adjusted R-square is significantly increased for all models. However, the cash holdings are not related to the efficiency of high-cash holding firms for these two stock exchanges. The contribution of cash holdings to firm efficiency is higher, and even double for a developed market compared with a developing market (Bursa Malaysia), which shows that the development stage of a country impacts on cash holdings’ contribution to firm efficiency. The second objective is to examine the valuation of shareholders from the value of additional cash holdings, given the existence of an optimal cash level. The value of additional cash holdings is higher for high-cash holding firms than for respect to lowcash holding firms. It is explained by a higher contribution of cash holdings to firm’s efficiency for high cash holding firm, which shows that shareholders do include the efficiency generated by cash holdings into their valuation. Besides, an optimal cash level is not statistically significant in shareholders’ valuation. The last objective in this study is to investigate the relevant financial ratios and risk factors that impact on the decisions on cash holdings. Generalized moment method (GMM) estimation is employed to investigate the impact of previous cash holdings on current stages. The results of GMM estimation show liquidity and repayment ability factors are significantly related with cash ratio for listed firm in KOSE and Bursa Malaysia. Whereas, risk factors only significant for high-cash holding firms in KOSE and low-cash holding firms in Bursa Malaysia. Thus, firm efficiency, risk factors and cash holdings are all connected. Overall, the findings show that the roles and values of cash holdings in Malaysia and South Korea are akin to each other’s. Higher cash holdings of a firm contribute to its higher firm efficiency and the dollar cash is judged at a higher value by shareholders. For shareholders, agency cost should be less worrying than the loss that a firm faces in default.